PERAN PERSONIL SEKOLAH DALAM MENGATASI PELANGGARAN DISIPLIN PESERTA DIDIK DI SMK NEGERI 4 PADANG - Astuti, Ria Witri; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
The problem in this research is: The role of school personnel to attack students discipline offenses in SMK Negeri 4 Padang views of: 1) The role of school personnel to attack students discipline offenses Â through a disciplined approach and 2) the role of school personnel to attack students discipline offenses through guidance and counseling approaches. This research is a descriptive. The population was mostly the teachers, amounts 101 people. Samples were selected by purposive sampling technique, so the total sample of 50 people. Data collection by using a questionnaire, in a statistic descriptive with a percentage formula. The research results revealed that: 1) The role of school personnel to attack students discipline offenses through a disciplined approach included in either category, 2) The role of school personnel to attack students discipline offenses through guidance and counseling approach included in either category. Based on the results of the research, the role of school personnel to attack students discipline offenses in SMK Negeri 4 Padang can be categorized either. The authors suggest to all school personnel more attention and improve their performance to achieve the learning process effective and efficient especially to attack student discipline offenses.